Fighting for the peasantry: The communists and the land collectivization during the Spanish Civil War - Puig Vallverdú, Guillem (Hispania Nova, 2021)
During the Spanish Civil War, there was a land collectivisation process that occupied the whole rear guard. The Spanish communists, despite defending the collectivisation, posted for her governmental control and the support to the small property. This text explores, on the one hand, the main theoric lines from Marxism and his influence in the Spanish Marxist debates about the agrarian question. In addition, this article investigates the changes of stances of the agrarian trade unions about collectivisation and the efforts from communists to leading them while the government power was being restored during the war.